Characterization of miR‐126‐3p and its Target Talin2 in the Bovine Corpus Luteum during the Oestrus Cycle. Issue 6 (22nd September 2014) - Dai, L; Xu, J; Liu, S; Ma, T; Zhu, Y; Xu, F; Gao, Y; Yuan, B; Wang, S; Zhang, Y; Sun, G; Zhang, J
Contents Although clear advances have been made in understanding of gene transcriptional regulation in the corpous luteum (CL) during the oestrous cycle, little is known about the involvement of microRNAs (miRNAs) in this physiological process. In the present study, expression of miR‐126‐3p was preliminarily detected in bovine CL throughout the oestrous cycle, while the expression during the middle or late stages was significantly more abundant (p < 0.01) than that during the early or regressed stages. Localization of miR‐126‐3p was subsequently observed in large and small luteal cells during the oestrous cycle in cattle. Meanwhile, to further investigate the function of miR‐126‐3p, its potential targets and responsive elements were determined and evaluated. It was revealed that miR‐126‐3p could target talin2 (TLN2) directly by binding the responsive element within the 3′‐UTR. Quantitative analysis of TLN2 at mRNA and protein level also suggested that there was an inverse correlation between miR‐126‐3p and TLN2 at the developmental luteal stages in cattle. Collectively, these results demonstrated that difference in the expression pattern and location of miR‐126‐3p occurred at different stages of the bovine CL and that miR‐126‐3p acted as an important regulator of TLN2, suggesting their putative involvement in the development of bovine CL during the oestrous cycle.